Engineering small molecule nanodrugs to overcome barriers for cancer therapy. Issue 3 (26th July 2020) - Ma, Yuan; Mou, Quanbing; Yan, Deyue; Zhu, Xinyuan
Abstract: Small molecule nanodrugs consisting of pure drugs, drug‐drug dimers, drug‐drug conjugates, or drug derivatives could realize drug delivery by themselves without the aid of carriers, which have received abundant attention in recent decades. Avoiding the use of additional carriers, the yielded small molecule nanodrugs hold the following advantages: (a) high drug loading capacities (some of them could even reach up to 100%); (b) precise and tunable drug loading ration; and (c) no carrier‐induced long‐term toxicity. The past decade has witnessed rapid growth and advancements in this field. In this review, we will briefly introduce both in vitro "barriers" and in vivo barriers for drug delivery, and then summarize the most recent development of small molecule nanodrugs from the point of view how to engineer small molecule nanodrugs to overcome these barriers. Abstract : Engineering of small molecule nanodrugs with high drug loading capacities, precise drug loading ration, and tunable size and morphology to overcome both in vitro "barriers" and in vivo barriers for cancer therapy has been summarized.